From unknown to known: Identification of the remains at the mausoleum of fosse Ardeatine. Issue 6 (November 2018) - Pilli, Elena; Boccone, Silvia; Agostino, Alessandro; Virgili, Antonino; D'Errico, Giancarlo; Lari, Martina; Rapone, Cesare; Barni, Filippo; Moggi Cecchi, Jacopo; Berti, Andrea; Caramelli, David
Abstract: During the Second World War, on 24th March 1944, 335 Italians were massacred near Rome by the occupying forces of Nazi Germany. Four months later forensic examination led to the identification of 323 out of 335 victims. After approximately 60 years, the identification of the remaining unidentified twelve victims began with anthropological and genetic analysis carried out by a team of Italian forensic experts. Anthropological analysis was performed in field in order to confirm the sex of each victim and verify the presence of only one individual in each grave for a correct sampling. Selected bone fragments for each individual were then collected and transferred to the laboratory for genetic analysis. Although the anthropological ante mortem information was limited, morphological and metrical data was collected for a possible future identification of the victims. Subsequently, the typing of autosomal loci, Y-STR and mtDNA D-loop region of all bone and available reference samples was conducted. LR and cumulative LRs obtained from autosomal STR and Y-STR results confirmed the alleged relationship between three victims and their relatives with values over 10 4 (one sample) and 10 6 (two samples). Therefore, the genetic analysis offered the families the possibility of replacing the number of the grave with the name of the victim. Highlights: During the Second World War, 335 civilians and Italian military personnel were killed near Roma. Some months later forensic examination led to the identification of 323 out of 335 victims. After about 60 years, the identification of the unidentified twelve victims began with anthropological and genetic analysis. The analyses offered the families the possibility of replacing the number of three graves with the name of the martyr.